Patient-Oriented SCORAD (PO-SCORAD): a new self-assessment scale in atopic dermatitis validated in Europe - Stalder, Jean François; Barbarot, S.; Wollenberg, A.; Holm, E. A.; De Raeve, L.; Seidenari, S.; Oranje, A.; Deleuran, M.; Cambazard, F.; Svensson, A.; Simon, D.; Benfeldt, E.; et al. (Allergy, 2011)
Background:Patient-oriented medicine is an emerging concept, encouraged by the WorldHealth Organization, to greater involvement of the patient in the management of chronicdiseases. The Patient-Oriented SCORing Atopic Dermatitis (PO-SCORAD) index is aself-assessment score allowing the patient to comprehensively evaluate the actual courseof atopic dermatitis (AD), using subjective and objective criteria derived mainly from theSCORAD, a validated AD severity clinical assessment tool.Objectives:To validate the PO-SCORAD index in a large European population ofpatients exhibiting all forms of AD severity by assessing its correlation with theSCORAD index.Patients/methods:Four hundred and seventy-one patients (185 adults, 286 children) con-sulting for AD in hospitals from 9 European countries were recruited. The investigatorsand the patients used the SCORAD and PO-SCORAD scales, respectively, to assess ADseverity at inclusion (D0) and 28 ± 7 days later (D28).Results:Patient-Oriented SCORing Atopic Dermatitis and SCORAD scores were signifi-cantly correlated at D0 [r= 0.67 (95% CI: 0.62; 0.72),P< 0.0001]. Consistency was con-firmed at D28, with a stronger linear correlation between both scales [r= 0.79 (95% CI:0.75; 0.83),P< 0.0001]. Absolute changes from baseline in SCORAD and PO-SCORADscores were also significantly correlated [r= 0.71 (95% CI: 0.64; 0.76),P< 0.0001].Although no specific intervention was investigated, AD improved over the study, with adecrease of PO-SCORAD and SCORAD scores from D0 to D28 by)19.19% and)24.39%,respectively. The consistency of the correlations was similar in the adult and children groups.Conclusions:This study validated the use of PO-SCORAD to self-assess AD severityand demonstrated its good correlation with SCORAD.